Activity Modification and Knee Strengthening for Osgood-Schlatter Disease: A Prospective Cohort Study. Issue 4 (6th April 2020) - Rathleff, Michael S.; Winiarski, Lukasz; Krommes, Kasper; Graven-Nielsen, Thomas; Hölmich, Per; Olesen, Jens Lykkegard; Holden, Sinéad; Thorborg, Kristian
Background: Osgood-Schlatter disease (OSD) affects 1 in 10 adolescents. There is a lack of evidence-based interventions, and passive approaches (eg, rest and avoidance of painful activities) are often prescribed. Purpose: To investigate an intervention consisting of education on activity modification and knee-strengthening exercises designed for adolescents with OSD. Study Design: Case series; Level of evidence, 4. Methods: This study included 51 adolescents (51% female; age range, 10-14 years) with OSD. The 12-week intervention consisted of an activity ladder designed to manage patellar tendon loading and pain, knee-strengthening exercises, and a gradual return to sport. The primary outcome was the global reporting of change at 12 weeks, evaluated with a 7-point Likert scale (successful outcome was considered "much improved" or "improved"). Additional endpoints were at 4, 8, 26, and 52 weeks. Secondary outcomes included the Knee injury and Osteoarthritis Outcome Score (KOOS), objective strength, and jump performance. Results: Adolescents reported a mean pain duration of 21 months at enrollment. After 12 weeks, 80% reported a successful outcome, which increased to 90% at 12 months. At 12 weeks, 16% returned to playing sport, which increased to 69% at 12 months. The KOOS subscores of Pain, Activities of Daily Living, Sport and Recreation, and Quality of Life improved significantly (7-20 points), and there were improvements in knee extension strength (32%; P < .001), hip abduction strength (24%; P < .001), and jumping for distance (14%; P < .001) and height (19%; P < .001) at 12 weeks. Conclusion: An intervention consisting of activity modification, pain monitoring, progressive strengthening, and a return-to-sport paradigm was associated with improved self-reported outcomes, hip and knee muscle strength, and jumping performance. This approach may offer an alternative to passive approaches such as rest or wait-and-see, often prescribed for adolescents with OSD. Registration: NCT02799394 (ClinicalTrials.gov identifier)